TEACHING VOCABULARY BY USING FLASHCARD MEDIA AT THE FIFTH GRADE ELEMENTARY SCHOOL - Rahmayanti, Rahmayanti; Luardini, Maria; Asi, Natalina (Journal Compound: Improving the Quality of English Education, 2020)
The aims of this research is to describe the teaching vocabulary by using flash cards media at the five grade students of SDN Pasar lama 3 Banjarmasin. It is conducted to know how the implementation of flash cards on the teaching English media in vocabulary with using word flashcards and picture flash cards by the teacher. The researcher will teach in V B class. It is caused the teacher choose this class to the researcher. This class consist of 32 students. The research design is descriptive qualitative research. The result of research is found that the students’ problem in using word flashcard media in teaching and learning process in the classroom with 32 students. there are 10 students who get score 60 or average. They still have difficulty with using word flash cards. and the second observation, the teacher used picture flashcard media in teaching and learning process in the classroom with 32 students. The all students understand the meaning in the picture flashcard shown by the teacher. The teacher give students score is very good with 70 - 100 score because the students can pass the KKM (Kriteria Ketuntasan Minimal). Based on the result, the researcher suggested that the students should learn more about vocabulary with using flash cards.